2019
DOI: 10.3174/ajnr.a6043
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Jet Velocity in Venous Flow after CSF Drainage: Assessing Hemodynamic Causes of Pulsatile Tinnitus

Abstract: Background and Purpose Idiopathic intracranial hypertension (IIH) is commonly associated with transverse sinus stenosis - a venous cause of pulsatile tinnitus (PT). In IIH patients, CSF drainage via lumbar puncture (LP) decreases intracranial pressure, which relieves the stenosis, and may provide at least temporary cessation of PT. The objective of this study is to evaluate changes in venous blood flow caused by lowered intracranial pressure in PT patients to help identify the cause of PT. Materials and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…A flow jet in the poststenotic region, which indicates a high velocity, has been reported by some previous studies, 8 , 20 and the results were consistent with ours. Haraldsson et al 21 found that the flow jet velocity was reduced after cerebrospinal fluid drainage, which may be caused by the expansion of the stenosis after lumbar puncture. Because the flow jet is directly related to the pressure gradient, the color of the poststenotic flow jet according to the color scale can reflect CVPG, with red coloration in the venous sinus potentially indicating a high CVPG.…”
Section: Discussionmentioning
confidence: 99%
“…A flow jet in the poststenotic region, which indicates a high velocity, has been reported by some previous studies, 8 , 20 and the results were consistent with ours. Haraldsson et al 21 found that the flow jet velocity was reduced after cerebrospinal fluid drainage, which may be caused by the expansion of the stenosis after lumbar puncture. Because the flow jet is directly related to the pressure gradient, the color of the poststenotic flow jet according to the color scale can reflect CVPG, with red coloration in the venous sinus potentially indicating a high CVPG.…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors have suspected a need to decompress the sigmoid sinus, 27 other studies have reported that eradicating flow pathologies at the prominent sinus junction reduces flow amplitude. 5,17,18 Furthermore, the operative change in jugular outflow volume is insignificant based on current Doppler outcomes. This may be due to the regulation of flow dynamics via the external jugular and vertebral pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It may imply that the dominance of the JF may potentially predispose to the development of PT to some extent, which might be associated with alterations of hemodynamics around the JF region. 22,23 However, this potential mechanism is still undefined and deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%